Environmental sustainability as an indicator of ecosystem reliability - Madzhd, Svitlana; Yakymenko, Igor; Nychyk, Oksana (My University, 2025)
The intensive flow of pollutants into ecosystems leads to their structural and functional changes. In such anthropogenically transformed ecosystems, the mechanisms of balanced functioning are disrupted, which leads to a loss of ecological sustainability. The paper examines the issue of the established response of the biotic component of the ecosystem to the impact of anthropogenic pollutants. It is proved that the biotic component of ecosystems is a reliable indicator of their ecological sustainability (Madzhd, 2024; Isaenko and Cherniak, 2019). It is noted that the study of the levels of reactions of living organisms in ecosystems and their thresholds to the harmful effects of anthropogenic pollutants allows developing a system for assessing the level of their environmental sustainability. The authors have developed a system for assessing the ecological sustainability of ecosystems based on studies of the viability of their biotic component. The need to develop a system for assessing the level of ecological sustainability of ecosystems is due to the need to implement measures aimed at ensuring their reliability in the face of high anthropogenic threats. The results of the research have shown that the biotic component of ecosystems allows to reliably reflect the level of their ecological sustainability, which is an informative indicator of their ecological reliability. The paper proves that the system for assessing the ecological sustainability of anthropogenically loaded ecosystems developed by the authors is a highly informative indicator of determining the level of their ecological reliability and can be successfully applied in the system of managing the ecological reliability of anthropogenically loaded ecosystems.
Keywords: ecosystems; ecological sustainability; ecosystem reliability; кафедра екології та екоменеджменту; антропогенне забрудненя; екологічна стійкість екосистем